A phenolic glycoside from Moringa oleifera Lam. improves the carbohydrate and lipid metabolisms through AMPK in db/db mice. (1st May 2020) - Bao, Yifan; Xiao, Jianbo; Weng, Zebin; Lu, Xinyi; Shen, Xinchun; Wang, Fang
Highlights: A phenolic glycoside from Moringa oleifera Lam. can ameliorate metabolic syndrome in db/db mice. Niazirin effectively regulated energy homeostasis. Niazirin improved hepatic carbohydrate metabolism in db/db mice through AMPK pathway. Niazirin reduce fatty acid synthesis and induce fatty acid oxidation in db/db mice through AMPK pathway. Abstract: The increasing incidence of metabolic syndrome requires more functional food products with low cost and excellent effects to assist treatment. The crude extract of Moringa oleifera Lam. showed excellent hypoglycemic activity. The current study was designed to investigate the effects and mechanism of niazirin, a bioactive component from Moringa oleifera Lam. seed, on diabetic metabolic syndrome. C57BL/6J mice were treated daily with 5 mL/kg/body weight (BW) of saline, while db/db mice were similarly treated with 5 mL/kg/BW of saline, 10 and 20 mg/kg/BW of niazirin, respectively. Results indicated that niazirin could significantly reduce body weight, water and food intake, improve hyperglycemia, insulin resistance, inflammation, carbohydrate and lipid metabolism, non-alcoholic fatty liver. Furthermore, niazirin improved the hepatic energy metabolism via AMPK signaling pathway. Our study provides an evidence of an edible plant product, niazirin, may help in the treatment of metabolic syndrome.